Incomplete response to artificial tears is associated with features of neuropathic ocular pain. Issue 6 (16th September 2015) - Galor, Anat; Batawi, Hatim; Felix, Elizabeth R; Margolis, Todd P; Sarantopoulos, Konstantinos D; Martin, Eden R; Levitt, Roy C
Abstract : Aims: Artificial tears are first-line therapy for patients with dry eye symptoms. It is not known, however, which patient factors associate with a positive response to therapy. The purpose of this study was to evaluate whether certain ocular and systemic findings are associated with a differential subjective response to artificial tears. Methods: Cross-sectional study of 118 individuals reporting artificial tears use (hypromellose 0.4%) to treat dry eye-associated ocular pain. An evaluation was performed to assess dry eye symptoms (via the dry eye questionnaire 5 and ocular surface disease index), ocular and systemic (non-ocular) pain complaints and ocular signs (tear osmolarity, tear breakup time, corneal staining, Schirmer testing with anaesthesia, and eyelid and meibomian gland assessment). The main outcome measures were factors associated with differential subjective response to artificial tears. Results: By self-report, 23 patients reported no improvement, 73 partial improvement and 22 complete improvement in ocular pain with artificial tears. Patients who reported no or partial improvement in pain with artificial tears reported higher levels of hot-burning ocular pain and sensitivity to wind compared with those with complete improvement. Patients were also asked to rate the intensity of systemic pain elsewhere in the body (other than the eye). Patients who reported no or incomplete improvement with artificial tears had higher systemic pain scores compared with those with complete improvement. Conclusions: Both ocular and systemic (non-ocular) pain complaints are associated with a differential subjective response to artificial tears.